Memórias de juventudes: experiências educativas no/do hip-hop - Romulo Pereira Silva (2018)
This research aims to dialogue with subjects who experienced the Hip Hop Movement in Belo Horizonte in their youth, seeking to understand to which extent this socializing experience had an impact on their lives. This study sought to establish a relationship between Hip Hop socializing experiences and academic/professional socializing dynamics experienced by participants, trying to grasp the meanings of the movement for them. Qualitative research was developed since this approach allows us to access some aspects of the reality that are based on symbolism and meanings. Along with a review of the literature, exploratory research was carried out to trace the movement history and potential participants who had an intense experience within Hip Hop movement of the 1990s in the capital of Minas Gerais. It was a period in which this very movement was being consolidated in the city. Interviews were carried out with six adult participants who were adult Black people. These narrative interviews aimed to grasp the interpretations and meanings attributed by the subjects to their previous experiences within the movement and its impacts on their current lives. Data categorization and analysis were made in the light of theoretical references of the sociology of education and the sociology of youth, having categories as "experience" and "socialization" as landmarks of the analytical understanding. Finally, it was possible to perceive that the marks left by the participation in the hip-hop movement were not homogenous, differing in intensity and resonance in various dimensions of the lives of subjects. However, the hip-hop movement was seen as an essential experience in the construction of their identities and of their learning bringing to them artistic skills, values, and a critical view regarding their social contexts. As a socializing institution, this participation also strongly influenced the live trajectories of the participant subjects